Newly introduced changes in the European standard PN-EN 13053:2020-05 Ventilation for building – Air handling units – Rating and performance for units, components and sections. Overview of the main changes - Szczęśniak, Sylwia (Instal, 2020)
The article presents the most important changes in the European version of standard no. PN-EN 13053:2020-05 Ventilation for building – Air handling unists – Rating and performance for units, components and sections. Due to the large number of changes introduced, the article contains only those that directly relate to the measurements and characteristics. It does not contain comments of the quoted sections and diagrams. Those that seems to be incorrect or incomplete were marked. Much of the content included in the standard needs separate explanations or discussions.
Keywords: nternal specific fan power of ventilation components; heat recovery exchangers; air handling units categories